2008
DOI: 10.1007/s11104-008-9682-5
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids from the pasture grass Brachiaria humidicola and one of their methyl esters as inhibitors of nitrification

Abstract: The tropical pasture grass, Brachiaria humidicola (Rendle) Schweick, produces nitrification inhibitory compounds (termed biological nitrification inhibitors or BNIs) in its shoot and root tissues and releases BNIs from its roots. In the present study, two BNI compounds were isolated and identified from the shoot tissue of B. humidicola using activity-guided fractionation. The recombinant Nitrosomonas europaea containing luxAB genes derived from the bioluminescent marine gram-negative bacterium Vibrio harveyi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 31 publications
1
60
1
4
Order By: Relevance
“…Crude extract of root exudates containing BNI activity showed an inhibitory effect of similar strength on both enzymatic pathways (Table 1; Table S2), indicating that other BNIs released from roots have a mode of action different from that of brachialactone. Recently, linolenic acid, a major BNI compound present in the leaf tissue of B. humidicola, was shown to block both AMO and HAO enzymatic pathways in a manner similar to BNI activity of crude root exudates, indicating the possibility of a single inhibitor affecting both the enzymatic pathways in Nitrosomonas (29). When a fatty acid binding protein, BSA, was added (after the addition of linolenic acid) to the Nitrosomonas pure cultures, a major portion of the inhibitory effect was removed, indicating the reversible nature of the inhibitory effect from linolenic acid (29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crude extract of root exudates containing BNI activity showed an inhibitory effect of similar strength on both enzymatic pathways (Table 1; Table S2), indicating that other BNIs released from roots have a mode of action different from that of brachialactone. Recently, linolenic acid, a major BNI compound present in the leaf tissue of B. humidicola, was shown to block both AMO and HAO enzymatic pathways in a manner similar to BNI activity of crude root exudates, indicating the possibility of a single inhibitor affecting both the enzymatic pathways in Nitrosomonas (29). When a fatty acid binding protein, BSA, was added (after the addition of linolenic acid) to the Nitrosomonas pure cultures, a major portion of the inhibitory effect was removed, indicating the reversible nature of the inhibitory effect from linolenic acid (29).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, linolenic acid, a major BNI compound present in the leaf tissue of B. humidicola, was shown to block both AMO and HAO enzymatic pathways in a manner similar to BNI activity of crude root exudates, indicating the possibility of a single inhibitor affecting both the enzymatic pathways in Nitrosomonas (29). When a fatty acid binding protein, BSA, was added (after the addition of linolenic acid) to the Nitrosomonas pure cultures, a major portion of the inhibitory effect was removed, indicating the reversible nature of the inhibitory effect from linolenic acid (29). The reducing power generated from the oxidation of hydroxylamine by HAO is Root exudate was collected from intact BH (CIAT 679) plants (root fresh weight of Ϸ20 g) using aerated solutions of 1 mM NH 4Cl, evaporated to dryness, extracted with methanol, and evaporated to dryness and dissolved in 200 L of dimethyl sulfoxide; 1 L of the crude extract was used for the determination of BNI activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds with BNI activity in the aerial parts of B. humidicola are unsaturated free fatty acids, linoleic acid (LA) and a-lenolenic acid (LN; Subbarao et al, 2008), which are relatively weak inhibitors of nitrification with IC 50 values of 3 3 10 25 M, whereas the IC 50 value of the synthetic nitrification inhibitor AT is 1 3 10 27 M. Both LA and LN inhibit Nitrosomonas by blocking of both the AMO and HAO enzymatic pathways . In addition, BNIs could also disrupt the electron transfer pathway via HAO to ubiquinone and cytochrome (which need to be maintained to generate reducing power, i.e.…”
Section: Biological Nitrification Inhibition (Bni)mentioning
confidence: 99%
“…First studies under controlled conditions by Subbarao et al (2008) indicated that LA maintained 50% of its inhibitory effect in terms of NO 3 − produced per g dry soil after 120 days, whereas the BNI effect of LN was stable until the end of the incubation period (4 months). Since it was observed that a major BNI effect in Bh pastures can be established within 3 years , it is also likely that next to the active release of BNI substances root decomposition could contribute to the accumulation of BNI products in soil.…”
Section: Introductionmentioning
confidence: 99%